Green Accounting Intervens Corporate Governance And Environmental Perfor-mance On Financial Performance - Hamzah, M. Imron; Suripto, Suripto; Holiawati, Holiawati (Jurnal Neraca Peradaban, 2025)
This study aims to analyze empirical evidence of green accounting as an intervening variable in the influence of corporate governance and environmental performance on financial performance in energy sector companies listed on the Indonesia Stock Exchange during the 2021-2023 period. This research adopts a quantitative and associative approach. The population in this study consists of 83 energy sector companies listed on the Indonesia Stock Exchange in 2021-2023. The sample was selected using purposive sampling, resulting in 53 companies over three years, yielding 159 data points. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results show that corporate governance and environmental performance have a direct, positive, and significant impact on green accounting. Additionally, corporate governance, environmental performance, and green accounting positively and significantly affect financial performance. Green accounting serves as an intervening variable that strengthens the relationship between corporate governance, environmental performance, and financial performance. This study provides managerial implications, emphasizing the importance of strengthening corporate governance, environmental performance, and the implementation of green accounting to enhance financial performance and support sustainability. Furthermore, future research is encouraged to expand the scope to other industrial sectors, integrate external factors such as regulations and organizational culture, and apply a longitudinal approach to understand the long-term impact of green accounting on corporate financial sustainability. These findings advocate for the development of standardized reporting policies and investment in environmentally friendly technologies to reinforce the relationship between sustainability aspects and financial performance.